2013
DOI: 10.1021/ja308784w
|View full text |Cite
|
Sign up to set email alerts
|

Distinct CCK-2 Receptor Conformations Associated with β-Arrestin-2 Recruitment or Phospholipase-C Activation Revealed by a Biased Antagonist

Abstract: Seven-transmembrane receptors (7TMRs), also termed G protein-coupled receptors (GPCRs), form the largest class of cell surface membrane receptors, involving several hundred members in the human genome. Nearly 30% of marketed pharmacological agents target 7TMRs. 7TMRs adopt multiple conformations upon agonist binding. Biased agonists, in contrast to non-biased agonists, are believed to stabilize conformations preferentially activating either G-protein- or β-arrestin-dependent signaling pathways. However, proof … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 67 publications
5
40
1
Order By: Relevance
“…A compound shown to physically interact with the ligand binding pocket of CXCR4 effectively inhibited the response in all signal transduction and functional receptor assays tested with consistent relative potencies, while compounds that did not interfere with agonist binding showed no or only very limited effect (Fig 5). Biased GPCR ligands, including antagonists that preferentially inhibit one functional or signaling pathway over the other have been described for other GPCRs [30, 31] and raise general interest since they might evoke less side effects in clinical settings [32]. Our data, however, indicate that compounds commonly used to interrupt CXCL12/CXCR4 interaction display no bias in activity when tested in functional assays relevant for CXCR4.…”
Section: Discussionmentioning
confidence: 71%
“…A compound shown to physically interact with the ligand binding pocket of CXCR4 effectively inhibited the response in all signal transduction and functional receptor assays tested with consistent relative potencies, while compounds that did not interfere with agonist binding showed no or only very limited effect (Fig 5). Biased GPCR ligands, including antagonists that preferentially inhibit one functional or signaling pathway over the other have been described for other GPCRs [30, 31] and raise general interest since they might evoke less side effects in clinical settings [32]. Our data, however, indicate that compounds commonly used to interrupt CXCL12/CXCR4 interaction display no bias in activity when tested in functional assays relevant for CXCR4.…”
Section: Discussionmentioning
confidence: 71%
“…As a consequence, N-acetyl-GIP has a less number of interactions with helices 6 and 7 compared to GIP. These results, together with data showing that helices 6 and 7 in G-protein coupled receptors are essential for stabilization of the active conformation of receptors, may explain atypical activity of N-acetyl-GIP analogue (Hollenstein et al, 2014;Audet and Bouvier, 2012;Magnan et al, 2013). So, it is plausible that the two agonists may stabilize different conformations of the GIPR, each of which having distinct ability to trigger signals.…”
Section: Discussionmentioning
confidence: 79%
“…Multiple Binding Sites at the Chemokine Receptor CCR2 Magnan et al, 2013). Notably, it has been reported that some CCR2 antagonists are capable of discriminating between different functional states of the receptor (Kredel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%